Recent high-precision mass measurements with the Penning trap spectrometer ISOLTRAP - Herfurth, Frank; Kluge, Heinz-Jürgen (The European physical journal. A, Hadrons and nuclei, 2005)
.The Penning trap mass spectrometer ISOLTRAP has to date been used for the determination of close to 300 masses of radionuclides. A relative mass uncertainty of 10-8 can now be reached. Recent highlights were measurements of rp-process nuclides as for instance 72-74Kr or superallowed β emitters like 22Mg, 74Rb and 34Ar. The heaviest nuclides measured so far with ISOLTRAP are neutron-rich radium and francium isotopes. An overview of ISOLTRAP mass measurements and details about the recent experiment on 229-232Ra and 230Fr are presented.